Katanin P60 and P80 in papillary thyroid carcinoma patients: Indicators for exacerbated tumor features and worse disease‐free survival. Issue 12 (3rd December 2020) - Chen, Qinggui; Lin, Fusheng; Lin, Ende; Huang, Qinghe; Wu, Guoyang
Abstract: Background: This study aimed to explore the clinical implications of katanin P60 and P80 (katanin P60/P80) regarding their correlations with clinicopathological features and survival profiles in papillary thyroid carcinoma (PTC) patients. Methods: Tumor tissue and paired adjacent tissue specimens were obtained from 172 PTC patients who underwent lobectomy or thyroidectomy. Besides, immunohistochemistry assay and immunoreactive (IR) score (multiplying staining intensity score by density score) were used to determine katanin P60/P80 expressions. According to IR score (from 0 12), katanin P60/P80 expressions were classified as low (IR score 0 3) and high (IR score 4 12) expressions. Results: Both katanin P60/P80 expressions were highly expressed in tumor tissue compared with adjacent tissue. Besides, tumor katanin P60 expression positively correlated with tumor katanin P80 expression. Tumor katanin P60 high expression correlated with larger tumor size, extrathyroidal invasion, advanced pT stage, pN stage, and pTNM stage, while no correlation of tumor katanin P60 expression with age or gender was observed; tumor katanin P80 high expression correlated with advanced pN stage and pTNM stage, whereas there was no correlation of tumor katanin P80 expression with age, gender, tumor size, extrathyroidal invasion, or pT stage. Furthermore, both tumor katanin P60/P80 high expressions correlated with shorter accumulating disease‐free survival. As for overall survival (OS), neither tumor katanin P60 nor P80 expression correlated with OS. Conclusion: Katanin P60/P80 measurement might assist with tumor management and prognosis surveillance in PTC patients.